Implementation of Literacy and Numeracy through Media Smart Apps Creator (SAC) in Elementary School Student - Argita Imanning Tyas; Sukartono; Fitri Puji Rahmawati; Minsih; Choiriyah Widyasari (Universitas Pendidikan Ganesha, 2022)
The literacy and numeracy skills of elementary school students are relatively low this is evidenced by the low standard scores of students. Teachers should know students' literacy and numeracy skills to make it easier to prepare for AKM, so that research is held on the use of Smart Apps Creator (SAC) media for analysis of literacy and numeracy skills. This study aims to analyses the implementation and results of the analysis of literacy and numeracy skills through the use of Smart Apps Creator (SAC) media. The type of research is descriptive qualitative. The subjects of the study were the principal, the teacher of class V, and the students of class V. Data collection techniques are tests, interviews, observations, and documentation. Test the validity of the data using source triangulation and engineering triangulation. Analysis of research data is interactive analysis. The results of the study are first, the implementation of analysis activities includes three stages, namely the teacher preparation stage to prepare questions applied to the Smart Apps Creator (SAC) media, the implementation stage of students doing questions through the Smart Apps Creator (SAC) media, the final stage of the teacher analysing student score results. Second, the results of the analysis show most students have reached the minimum standards of educational units and class averages of categories in both literacy and numeracy aspects. The conclusion is Smart Apps Creator (SAC) help teacher to analyse literacy and numeracy skills. Therefore teachers should develop skills in the field of technology.